Modifikasi Limitter Temperatur pada Element Pemanas Mesin Pengering Batik terhadap Efektivitas Pengeringan - Yasin Aushaf Aburrahman; Adinda Sekar Ludwika; Ibnu Abdul Rosid; Surotun Nabawiyah (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The batik drying process is an important stage that affects product quality, production time, and energy efficiency. Drying using sunlight is still widely applied; however, it has limitations because it depends on weather conditions, resulting in inconsistent drying times. This study aims to analyze the effect of modifying the temperature limiter on the heating element of a batik drying machine on the effectiveness of the drying process. The research method used was a comparative experimental method with temperature variations of 40°C, 50°C, and 60°C. Each treatment was conducted with five repetitions. The observed parameters included drying time, fabric weight before and after drying, and the stability of the drying chamber temperature. The data were analyzed descriptively, and a One-Way ANOVA was planned to determine the effect of temperature variations on drying effectiveness. The results showed that increasing the temperature shortened the drying time. A temperature of 40°C resulted in an average drying time of 2 hours and 37 minutes, 50°C resulted in 1 hour and 32 minutes, while 60°C resulted in 60 minutes. Although 60°C provided the fastest drying time, 50°C resulted in the final fabric weight that was closest to the initial weight and was therefore considered the most optimal operating temperature.